Neurobehavioral effects of acute low-dose whole-body irradiation. (13th May 2021) - Bekal, Mahesh; Sun, Lue; Ueno, Susumu; Moritake, Takashi
Abstract: Radiation exposure has multiple effects on the brain, behavior and cognitive functions. It has been reported that high-dose (>20 Gy) radiation-induced behavior and cognitive aberration partly associated with severe tissue destruction. Low-dose (<3 Gy) exposure can occur in radiological disasters and cerebral endovascular treatment. However, only a few reports analyzed behavior and cognitive functions after low-dose irradiation. This study was undertaken to assess the relationship between brain neurochemistry and behavioral disruption in irradiated mice. The irradiated mice (0.5 Gy, 1 Gy and 3 Gy) were tested for alteration in their normal behavior over 10 days. A serotonin (5-HT), Dopamine, gamma-Aminobutyric acid (GABA) and cortisol analysis was carried out in blood, hippocampus, amygdala and whole brain tissue. There was a significant decline in the exploratory activity of mice exposed to 3 Gy and 1 Gy radiation in an open field test. We observed a significant short-term memory loss in 3 Gy and 1 Gy irradiated mice in Y-Maze. Mice exposed to 1 Gy and 3 Gy radiation exhibited increased anxiety in an elevated plus maze (EPM). The increased anxiety and memory loss patterns were also seen in 0.5 Gy irradiated mice, but the results were not statistically significant. In this study we observed that neurotransmitters are significantly altered after irradiation, but the neuronal cells in the hippocampus were not significantly affected. This study suggests that the low-dose radiation-induced cognitive impairment may be associated with the neurochemical in low-dose irradiation and unlike the high-dose scenario might not be directly related to the morphological changes in the brain.